VISUALIZATION OF TEMPERATURE FIELDS AROUND CURVED SURFACES BY THERMOVISION - KONIAR, Jan; BRODNIANSKA, Zuzana (Trends in education, 2012)
The present contribution described the experimental setup for visualization of temperature fields around curved surfaces by infrared camera. This experimental setup can be utilized as a didactic tool in educational process, for study of heat transfer processes in the Environmental Technology study programme, mainly in subjects as Process Mechanical Engineering, Energetic Changes, Energetic Machines and Equipment.
Keywords: heat transfer; temperature fields; infrared camera.